Antibacterial activity of epidermal layer of fishes against human pathogens - John, Shani; Patterson, Jameela (Indian Journal of Fisheries, 2012)
Diethyl ether, methanol and acetone extracts of epidermal layer of finfishes like Scomberoides tol, Sardinella longiceps, Nemipterus furcosus, Nemipterus marginatus and Nemipterus japonicus were assessed for antibacterial activity against ten human pathogens such as Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus mirabilis, Escherechia coli, Salmonella typhi, Streptococcus epidermidis, Bacillus cereus, Streptococcus pneumoniae, Enterobacter aeruginosa and Vibrio cholerae. The crude methanol extract of S. tol showed good antibacterial activity than that of S. longiceps, N. furcosus, N. marginatus and N. japonicus. The maximum zone of inhibition ranged between 8 mm against S. typhi and B. cereus. The extract which showed promising activity was partitioned and its activity was also assessed. The ethyl acetate phase of the partitioned extract showed wide spectral activity against all the ten human pathogens. The highest activity was observed against S. typhi (6 mm) and B. cereus (7 mm). Based on the activity, the extracts were further separated by column chromatography and the activity was assessed. The 100% ethyl acetate extract showed good antibacterial activity of 6 mm against S. typhi and 5 mm against P. mirabilis compared to the other phases